NURTURING SUSTAINABILITY THROUGH EDUCATION - MPRC, Pusat Media & Perhubungan Awam (USM, 2017)
USM, PENANG, 24 January 2017 – The right mix of spices will result in the preparation of tasty dishes; such was the parable drawn by the President of the International Association of Universities (IAU), Tan Sri Dato’ Dzulkifli Abdul Razak in highlighting the requirements for sustainability to be widely practiced and accepted.